Pharmaceutical care to pregnant women carrying human immunodeficiency virus - Geysa Aguiar Romeu; Larissa Varela de Paiva; Mariana Mota Moura Fé (Universidade de São Paulo, 2009)
The purpose of this present study was to know the pharmacoepidemiological profile of pregnant women carrying HIV, the prevention actions against vertical transmission, and evaluate the service respecting the patients' level of satisfaction. It was developed a quali-quantitative longitudinal study, with the sample being composed by pregnant women carrying HIV attended at the Pharmaceutical Care Service of a public hospital of Fortaleza - state of Ceará, during the period between January and September, 2007. The data were collected by means of follow-up cards, patients' medical history and, finally, interviews to verify the users' level of satisfaction related to the service. Twenty seven pregnant and parturient women have participated in the study. The mean profile found was of a single woman, aged in the range between 18 and 28 years, of Caucasian race or dark colored, with familial revenue below the minimum wage, having elementary or high school, and being unemployed. It was observed that 77.8% (n=21) of patients followed all prevention strategies against maternal-infant transmission. Twenty nine drug related problems have been detected, out of which 51.7% (n=15) were resolved. The general level of satisfaction respecting the Pharmaceutical Care Service was quite satisfactory. By means of the Pharmaceutical Care Service, the pharmacist professional effectively collaborates for the correct utilization of medications, and this action results directly in a decrease of HIV vertical transmission. Objetivou-se com o presente estudo conhecer o perfil farmacoepidemiológico das gestantes portadoras do vírus HIV, as ações de prevenção da transmissão vertical e avaliar o serviço quanto ao nível de satisfação das pacientes. Realizou-se estudo quali-quantitativo, longitudinal, sendo a amostra composta pelas gestantes portadoras do vírus HIV atendidas no Serviço de Atenção Farmacêutica de um hospital público de Fortaleza-CE, no período de janeiro a setembro de 2007. Coletaram-se os dados por meio de fichas de seguimento, prontuários das pacientes e, finalmente, entrevistas para verificar o nível de satisfação das usuárias em relação ao serviço. Participaram do estudo 27 gestantes e parturientes infectadas pelo HIV. O perfil encontrado foi de mulheres solteiras, na faixa etária de 18 a 28 anos, de cor branca ou parda, com renda familiar inferior a um salário mínimo, com ensino fundamental ou médio e desempregadas. Observou-se que 77,8% (n=21) pacientes seguiram todas as estratégias de prevenção da transmissão materno-infantil. Detectaram-se 29 problemas relacionados ao uso de medicamentos, dos quais 51,7% (n=15) foram resolvidos. O nível de satisfação geral em relação ao serviço de atenção farmacêutica foi bastante satisfatório. Por meio do serviço de atenção farmacêutica, o profissional farmacêutico colabora com a utilização correta dos medicamentos, podendo repercutir diretamente na redução da transmissão vertical do HIV.